Vállalati kapcsolatok és együttműködések a Széchenyi István Egyetemen: egy pilot kutatás eredményei - Kovács, Zsolt (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The investigation completed through the cooperation between the Széchenyi István University and the Educatio Kht. is based on depth interwievs conducted by employers. The study in question analyses the role of the institutional factors and the role of the re-gionality concerning the features of employment of the entrants. As a result of the investi-gation - as expected from employers' research - we are given a full picture concerning the employer's - functioning in the university area - requirements and experineces related to the entrants, concerning the requirements of the institutional cooperation, moreover con-cerning the importance of the regional aspects. The aim of the pilot research is to build up a research program model that specifies and illustrates those steps and methodological considerations that are aimed to give a hand for the higher education institutions to make career examinations in the employer environment relevant to them. On the other hand the intention of the research is to make more theoritical conclusions concerning the relation-ship of the labour market and the regionality.